MENINGKATKAN KARAKTER TANGGUNG JAWAB MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI MI I’ANATUSSHIBYAN 1 - Handayani, Wuri; Sa diyah, Maemunah; Suhandi, Tjetjep (ATTA`DIB, 2019)
This research aims to improve the character of student responsibility through the CTL (Contextual Teaching and Learning) approach to Fiqh subjects in MI I'Anatusshibyan 1. This type of research was used classroom action research methods with descriptive qualitative and quantitative descriptive types of Classroom Action Research (CAR). Data collection techniques are used observation, field notes, and documentation as a research instrument. The Observation were made on the character of student responsibility using the observation sheet. Character observation results of the responsibility of students in class I can be described at the pre-cycle stage, cycle I, and cycle II. From the implementation of pre-cycle obtained an average value of 1.55 or 38.94% in the less category, then carried out action in cycle I. The results of observation in the first cycle obtained an average value of 2.10 or 52.63% in the sufficient category. From the results of observation in the first cycle the researcher got several obstacles, then made repairs or improvements both at the planning stage, namely the RPP until the implementation stage in the second cycle. The results of observations in the second cycle obtained an average value of 3.02 or 75.52% in the good category. Therefore there was an increase in the character value of student responsibility from the pre-cycle stage to the second cycle of 1.46 or 36.57%. This proved that the CTL approach can improve the character of the responsibility of class I students at MI I’Anatusshibyan 1.